Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5ra21010k
|View full text |Cite
|
Sign up to set email alerts
|

Polylactide–hydroxyapatite nanocomposites with highly improved interfacial adhesion via mussel-inspired polydopamine surface modification

Abstract: The interfacial bonding between inorganic hydroxyapatite and organic polylactide could be significantly improved by introducing polydopamine surface coating on hydroxyapatite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…coated a layer of polydopamine on the surface of HAP nanorods, and found that the adhesion of polydopamine improved the interfacial binding strength of HAP/PLLA composite film. [ 171 ] Lai et al. modified the surface of HAP particles by coating stearic acid to improve the distribution and phase interface of HAP and polymer.…”
Section: A Type Of Bone Scaffold Materials With Both Mechanical and B...mentioning
confidence: 99%
“…coated a layer of polydopamine on the surface of HAP nanorods, and found that the adhesion of polydopamine improved the interfacial binding strength of HAP/PLLA composite film. [ 171 ] Lai et al. modified the surface of HAP particles by coating stearic acid to improve the distribution and phase interface of HAP and polymer.…”
Section: A Type Of Bone Scaffold Materials With Both Mechanical and B...mentioning
confidence: 99%
“…These surface modifications improve the dispersion and interfacial adhesion, but their practical applications are limited [ 14 ]. In recent years, the surface modification of nanofillers by mussel-induced dopamine (DA) has been a hot research topic for preparing organic–inorganic composites [ 15 , 16 ]. DA can self-polymerize and turn to polydopamine (PDA) on the surface of nanomaterials, which can enhance the dispersion of the added material by hydrogen bonding or Π-Π interactions with resin macromolecules, achieving a good affinity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this material-independent PDA-coating process was very easily, quickly, and efficiently achieved through base-triggered oxidation and polymerization of DA for surface functionalization of various substrates via a single-step process. This PDA ad-layer can be used as a platform for surface modification, including spontaneous deposition of different factors, as well as covalent immobilization of various growth factors and proteins [ 20 , 21 ]. A recent novel strategy to improve the physiological properties of various biomaterials involves the admixing of biological molecular dopamine (DA) and polydopamine (PDA) into the formulation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%